2015
DOI: 10.1007/s12263-015-0453-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphisms in one-carbon metabolism genes, Mediterranean diet and breast cancer risk: a case–control study in the Greek-Cypriot female population

Abstract: Single-nucleotide polymorphisms (SNPs) within genes of the one-carbon metabolism pathway have been shown to interact with dietary folate intake to modify breast cancer (BC) risk. Our group has previously demonstrated that the Mediterranean dietary pattern, rich in beneficial one-carbon metabolism micronutrients, protects against BC in Greek-Cypriot women. We aimed to investigate whether SNPs in the MTHFR (rs1801133 and rs1801131) and MTR (rs1805087) genes modify the effect of the Mediterranean dietary pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The initial search resulted in 136 articles, of which 102 articles were excluded at the title and abstract level. Thirty-four full-length articles were selected for further evaluation and 18 of these were excluded for the following reasons: examined diet as a predictor of breast density not cancer (n=3) (24)(25)(26), the combined effect of diet and physical activity was studied (n=2) (27,28), statistical methods other than those specified in our inclusion criteria were used (n=2) (29,30), and evaluated various forms of vegetarian diet (derived without using any dietary index or factor analysis) (n=1) (31), hormone levels rather than diet were studied (n=3) (32)(33)(34), the effect of diet on breast cancer markers at the molecular level were studied (n=5) (35)(36)(37)(38)(39), assessed the dietary intake of women during their adolescent years (n=1) (40), used an average/reference dietary pattern to derive the risk estimates (n=1) (41), one paper was identified by hand searching the selected articles (42). This resulted in the selection of 17 original research studies published between January 2013 and May 2017 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), where 13 of these used the posteriori approach while 2 of the 13 also included an a priori approach to identify dietary patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search resulted in 136 articles, of which 102 articles were excluded at the title and abstract level. Thirty-four full-length articles were selected for further evaluation and 18 of these were excluded for the following reasons: examined diet as a predictor of breast density not cancer (n=3) (24)(25)(26), the combined effect of diet and physical activity was studied (n=2) (27,28), statistical methods other than those specified in our inclusion criteria were used (n=2) (29,30), and evaluated various forms of vegetarian diet (derived without using any dietary index or factor analysis) (n=1) (31), hormone levels rather than diet were studied (n=3) (32)(33)(34), the effect of diet on breast cancer markers at the molecular level were studied (n=5) (35)(36)(37)(38)(39), assessed the dietary intake of women during their adolescent years (n=1) (40), used an average/reference dietary pattern to derive the risk estimates (n=1) (41), one paper was identified by hand searching the selected articles (42). This resulted in the selection of 17 original research studies published between January 2013 and May 2017 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), where 13 of these used the posteriori approach while 2 of the 13 also included an a priori approach to identify dietary patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Limitations of the study include the possible selection and the survival biases, which have previously been discussed [11,27,44]. In addition, the FFQ used in our study examined only 32 food and beverage items, which is a limited number for a typical FFQ.…”
Section: Discussionmentioning
confidence: 99%
“…TaqMan Universal PCR Master Mix and 30 ng of genomic DNA were used in a final reaction volume of 5 μl for each assay. Genotyping was performed using 384-well plates as described by Kakkoura et al [27]. The order of DNA samples from cases and controls on the 384-well plate was randomised, in order to ensure that samples from cases and controls were subjected to the same study conditions.…”
Section: Genotypingmentioning
confidence: 99%
“…MTR A2756G was investigated in ten different populations out of which it was identified as a risk factor in Iranian (Hosseini 2013) and Australian (Beetstra et al 2008) populations. In two populations, i.e., Greece (Kakkoura et al 2015) and China (He et al 2014), this polymorphism showed an inverse association with breast cancer risk while in other population, it showed a null association (Platek et al 2009;Weiwei et al 2014;He et al 2014). MTRR A66G was identified as a risk for breast cancer in a Russian population (Tao et al 2009), while it was shown to have an inverse association with Thai (Sangrajrang et al 2009;Sangrajrang et al 2010) and Australian (Beetstra et al 2008) populations.…”
Section: Introductionmentioning
confidence: 98%